2018
DOI: 10.20945/2359-3997000000084
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for new-onset diabetes mellitus after kidney transplantation (NODAT): a Brazilian single center study

Abstract: Objectives: This study aims to verify the new-onset diabetes after kidney transplant (NODAT) incidence in recipients within 1 year after kidney transplantation from a single center in Southern Brazil and to assess the associated conditions. Subjects and methods: A retrospective study of 258 postrenal transplant patients was performed. Demographic (gender, age, ethnic background) and clinical (origin of graft, associated infections, body mass index (BMI) at transplant time and 6 and 12 months after, causes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(29 reference statements)
4
7
1
Order By: Relevance
“…Polymorphisms in the IL7R (rs1494558) and MBL2 (rs2232365) genes were associated with a higher risk of NODAT among pooled Malaysian renal transplanted populations. Despite similar diagnostic criteria, high variability in the incidence of NODAT within 1 year posttransplantation has been reported in different populations [19][20][21]. The incidence of NODAT at one-year post-transplantation in our study was slightly higher [14] in their studies in single centres in Malaysia.…”
Section: Discussioncontrasting
confidence: 44%
“…Polymorphisms in the IL7R (rs1494558) and MBL2 (rs2232365) genes were associated with a higher risk of NODAT among pooled Malaysian renal transplanted populations. Despite similar diagnostic criteria, high variability in the incidence of NODAT within 1 year posttransplantation has been reported in different populations [19][20][21]. The incidence of NODAT at one-year post-transplantation in our study was slightly higher [14] in their studies in single centres in Malaysia.…”
Section: Discussioncontrasting
confidence: 44%
“…Lima et al reported it in their cohort study carried out in Brazil with 209 patients of whom 53 were afro-descendants. This characteristic showed a significant difference in its distribution between the group with NODAT and without the disease (30.2% vs 17.5%, p = 0.02), as it was seen in our study [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…is characteristic showed a significant difference in its distribution between the group with NODAT and without the disease (30.2% vs 17.5%, p � 0.02), as it was seen in our study [17].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…New-onset diabetes mellitus after transplantation (NODAT) refers to the detection of diabetes after a successful organ transplantation in patients who had not previously shown abnormal blood glucose levels before surgery. With the continuous developments and improvements in the field of organ transplantation, kidney transplantation has been carried out in an increasing number of patients; however, NODAT often occurs after kidney transplantation, with an incidence rate of 2-50% [1][2][3] . NODAT can lead to related complications, such as kidney transplant failure, cardiovascular disease and infection 4 , seriously endangering the quality of life and prognosis of patients with a kidney transplant, and increasing their economic burden.…”
Section: Introductionmentioning
confidence: 99%